Pudendal schwannoma: A case report and literature review - Mazzola, Clarisse R.; Power, Nicholas; Bilsky, Mark H.; Robert, Roger; Guillonneau, Bertrand (Canadian Urological Association Journal, 2014)
Schwannomas are benign nerve sheath tumours most often associated with the cranial nerves and the peripheral nerve system of the neck and extremities. Pelvic schwannomas are rare, with only about 25 cases reported. We report the case of a 34-year-old man referred for worsening pain of 10 years duration involving the right testicle and right penile shaft. Magnetic resonance imaging discovered a well-circumscribed pelvic tumour of 3.2 × 2.8 × 3.2 cm. Considering the possible complications involved in exposing the pudendal nerve during surgical resection, we performed an extensive literature search to aid preoperative planning. The most commonly described surgical approach for pelvic schwannomas has been open median laparotomy with transperitoneal dissection. To our knowledge, pudendal schwannomas have never been described in the literature. However, after considering the location and characteristics of the tumour, we chose laparoscopy because it offers the advantages of better visualization of anatomical structures with minimal invasiveness and faster recovery. At the 3-week follow-up, the patient described a significant decrease in pain and normal neurological and urological examinations.